2019
DOI: 10.3390/nano9111634
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial Growth of High-Quality and Crack-Free AlN Film on Sapphire Substrate with Nanometer-Scale-Thick AlN Nucleation Layer for AlGaN-Based Deep Ultraviolet Light-Emitting Diodes

Abstract: High-quality and crack-free aluminum nitride (AlN) film on sapphire substrate is the foundation for high-efficiency aluminum gallium nitride (AlGaN)-based deep ultraviolet light-emitting diodes (DUV LEDs). We reported the growth of high-quality and crack-free AlN film on sapphire substrate with a nanometer-scale-thick AlN nucleation layer (NL). Three kinds of nanometer-scale-thick AlN NLs, including in situ low-temperature AlN (LT-AlN) NL, oxygen-undoped ex situ sputtered AlN NL, and oxygen-doped ex situ sputt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Pits caused by the TDs or stacking faults as reported in previous studies are observed. [ 31–34 ] The threading dislocation densities of these three experimental samples, MQW1, MQW2, and MQW3, are of the order of 1–2 × 10 8 cm −2 , as shown in Figure . The V‐shaped pits are formed around the TDs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Pits caused by the TDs or stacking faults as reported in previous studies are observed. [ 31–34 ] The threading dislocation densities of these three experimental samples, MQW1, MQW2, and MQW3, are of the order of 1–2 × 10 8 cm −2 , as shown in Figure . The V‐shaped pits are formed around the TDs.…”
Section: Resultsmentioning
confidence: 93%
“…The V‐pit layer could reduce the leakage current, enhance the radiative recombination efficiency, and relieve the efficiency droop of GaN‐based LEDs. [ 31–34 ] The research results also show that the use of QD technology can effectively improve the luminous efficiency of GaN‐based green LEDs. [ 27–30 ] In this article, we modified the morphology of residual dislocations by using a compound V‐pit layer.…”
Section: Introductionmentioning
confidence: 96%
“…[32,33] Although, sapphire remains the dominant substrate material for the epitaxy of nitrides LEDs, because it allows lower dislocations densities and the best crystalline quality. [34] But the use of large Si substrates also attracts great interest due to its availability in the market at a lower cost. Further, the growth over Si could be useful to integrate nitrides with silicon standard electronics.…”
Section: Epitaxial Growth and Chip Processing Of Ledsmentioning
confidence: 99%
“…Another consideration is required since III-V alloy components have different lattice constants; therefore, an AlN buffer layer must be grown to replicate the substrate structure in order to avoid cracks and reduce dislocations [97]. The following layer on the hexagonal AlN must be designed to improve the LED technology and its efficiency [98].…”
Section: Substrate and Buffer Layermentioning
confidence: 99%